DESIGN SYSTEMS: ANALYSIS OF THE IMPACT ON THE DIGITAL AND PHYSICAL ENVIRONMENT - Novik, Hanna; Gnatiuk, Liliia; Yasenok, Serhii (Theory and practice of design, 2023)
The study of the application of design systems in the digital and physical spheres is presented. Focusing on the role function of the concept of design systems, the study reveals the evolution of this concept from its initial stages to modern strategies and methods. An analysis of previous research was carried out, including an overview of successful implementations of design systems in digital and physical environments, as well as challenges and advantages of their use. Examples of the application of design systems in various industries, such as manufacturing, construction, architecture and design, are considered, and the significance of their impact on increasing efficiency, consistency and quality of products in the digital and physical spheres is highlighted. The results of the study indicate the potential of design systems as a tool for optimizing development processes and improving user experience in the modern technological environment The growing complexity of digital and physical products leads to design inconsistencies that adversely affect user experience and brand perception. The purpose is to identify the peculiarities of implementing design systems in physical and digital environments. Research methodology: analysis of existing design systems. Research findings. Identification of the benefits of establishing a unified design system to enhance design consistency, reduce development time, and improve product perception by consumers. Scientific novelty. The establishment of the importance of integrating design systems to ensure unity in design and enhance the efficiency of the design process management. Practical significance. Providing recommendations for organizations to implement design systems to enhance user experience, reduce costs, and increase competitiveness.